2018
DOI: 10.1002/cncr.31265
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to accessing palliative care for pediatric patients with cancer: A review of the literature

Abstract: Although many of the 16,000 children in the United States diagnosed who are with cancer each year could benefit from pediatric palliative care, these services remain underused. Evidence regarding the barriers impeding access to comprehensive palliative care is dispersed in the literature, and evidence specific to pediatric oncology remains particularly sparse. The purpose of the current review was to synthesize the existing literature regarding these barriers and the strategies offered to address them. The aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
98
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 83 publications
(100 citation statements)
references
References 61 publications
(160 reference statements)
2
98
0
Order By: Relevance
“…Another proposed explanation in literature for the lack of timely PC provision is the shortage of clinicians capable to deliver PC to children with cancer. 40 In a survey of PC providers-physicians, nurses, and other staff members-one-third of respondents cited insufficient training in PC as a barrier to earlier PC integration. 41 The limited exposure to targeted PC education in residency and fellowship means hospitals do not have staff with the training to meet the palliative needs of pediatric oncology patients.…”
Section: Discussionmentioning
confidence: 99%
“…Another proposed explanation in literature for the lack of timely PC provision is the shortage of clinicians capable to deliver PC to children with cancer. 40 In a survey of PC providers-physicians, nurses, and other staff members-one-third of respondents cited insufficient training in PC as a barrier to earlier PC integration. 41 The limited exposure to targeted PC education in residency and fellowship means hospitals do not have staff with the training to meet the palliative needs of pediatric oncology patients.…”
Section: Discussionmentioning
confidence: 99%
“…Most PC services for children with cancer are rendered in the inpatient setting . The American Academy of Pediatrics recommends consideration of PC from diagnosis in children with cancer .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Most PC services for children with cancer are rendered in the inpatient setting. 7 The American Academy of Pediatrics recommends consideration of PC from diagnosis in children with cancer. 5 In particular, cancer patients near the end of life and their families would benefit from PC given the high mortality risk and degree of suffering.…”
Section: Introductionmentioning
confidence: 99%
“…66 Although well developed in survivorship care, pediatric palliative care still is very much a growing field, and opportunities to further emphasize research in this area remain. [67][68][69] International studies have shown various benefits of the earlier integration of palliative care in terms of QOL, health care use, levels of patient and caregiver distress, and even survival. 9,24,70,71 As a result, models to introduce earlier palliative care concurrent with standard oncology treatment have received increased recognition.…”
Section: Researchmentioning
confidence: 99%
“…Conversely, palliative care research has been growing, and many of the most recent clinically influential studies in the field have been centered around oncological diseases . Although well developed in survivorship care, pediatric palliative care still is very much a growing field, and opportunities to further emphasize research in this area remain . International studies have shown various benefits of the earlier integration of palliative care in terms of QOL, health care use, levels of patient and caregiver distress, and even survival .…”
Section: Introductionmentioning
confidence: 99%